A novel HLA‐A*02 allele, A*02:692, was identified by sequencing‐based typing. (13th November 2017) - Zhu, Y.‐L.; Han, B.; Chi, X.‐Y.; Hu, B.; Feng, Z.‐H.
Abstract : One nucleotide replacement at nucleotide 811 of HLA‐A*02:01:01:01 results in a new allele, HLA‐A*02:692 .